A novel transformation of a zirconium imido compound and the development of a new class of N3 donor heteroscorpionate ligand. - Howe, R; Tredget, C; Lawrence, S; Subongkoj, S; Cowley, A; Mountford, P (2006)
Reaction of the dimeric zirconium imido compound [Zr2(mu-NAr)2Cl4(THF)4] with tris(3,5-dimethylpyrazolyl)methyl silane very selectively gave [Zr{(Me2pz)2Si(Me)NAr}Cl3] (1), a highly active pre-catalyst for ethylene polymerisation; a more general and versatile route to N3 donor heteroscorpionate compounds was achieved via the protio ligand (Me2pz)2CHSi(Me)2N(H)iPr for which neutral and cationic organometallic Group 3 and 4 derivatives are reported (Ar = 2,6-C6H(3)iPr2).